GAMBARAN KUALITAS HIDUP LANSIA DENGAN HIPERTENSI DI INDONESIA: SYSTEMATIC REVIEW - La Ode Alifariki (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Background: Hypertension is the biggest health problem in the world, especially in developing countries. The purpose of the study was to describe the quality of life in the elderly with hypertension. The instrument used is a questionnaire, where this questionnaire was made by WHO, namely the World Health Organization Quality Of Life - Bref (WHOQOL-BREF). Data analysis technique with univariate and bivariate analysis. Methods: This systematic review was carried out using the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) statement, articles that have been published in Indonesian and have gone through a peer-review process in the 2010-2021 publication period. Relevant articles were searched for and collected. using Garuda and Google Scholar. The search keywords were matched with the Mesh terms for health studies. The keywords used vary, depending on the search engine used. In general, keywords focused on Elderly AND Hypertension OR High blood pressure AND Quality of Life. Results: The search returned 10,115 articles; after deleting duplicate articles, there were still 9,043 articles, of which 9,016 were deleted after filtering titles and abstracts, the remaining 27 articles were reviewed and checked for eligibility so that 22 articles were excluded because they were not full text. The final results were collected as many as 5 articles that met the inclusion criteria. Conclusion: various research results in this study provide a diverse picture of the quality of life of the elderly.